Maximum isometric hip adduction squeeze and abduction press strength values in men's rugby union players at select timepoints throughout a competitive season - O'Connor, C.; McIntyre, M.; Delahunt, E.; Thorborg, K. (The Journal of Strength and Conditioning Research, 2025)
The purpose of this research was to report hip adduction and abduction strength values in men's rugby union players at select timepoints throughout a competitive season and to examine if differences exist between time of season and hip-testing positions. This cross-sectional repeated measures study design consisted of 15 male rugby union players competing at senior club level. Maximum isometric hip adduction and abduction strength were measured using a ForceFrame in 3 testing positions at specific timepoints: start of preseason (T1), start of competitive season (T2), mid-season period 1 (T3), and mid-season period 2 (T4). At group level, hip adduction strength (N·kg-1) increased from T1 to T2 in all testing positions, with significant increases observed in the 0° hip-flexion short-lever position (p = 0.048), and 45° hip-flexion position (p = 0.032). No significant changes occurred in hip abduction strength (N·kg-1). Hip adduction:abduction strength ratio increased from T1 to T2, with a significant increase observed in the 0° hip-flexion short-lever position (p = 0.008). At individual level, large variations from baseline strength (N·kg-1) were observed between timepoints for hip adduction strength, abduction strength, and adduction:abduction strength ratio. In conclusion, the present study shows increases in hip adduction strength and hip adduction:abduction strength ratio from the start of preseason to the beginning of the competitive season, with no other significant changes in hip strength observed throughout the season. Individual and frequent hip strength monitoring throughout the season and a more individualized exercise prescription approach may be needed for rugby union players, in addition to a more generalized focus on improving adductor and abductor strength.